2013
DOI: 10.1038/gim.2013.43
|View full text |Cite
|
Sign up to set email alerts
|

Underutilization of Lynch syndrome screening in a multisite study of patients with colorectal cancer

Abstract: Purpose To examine Lynch Syndrome (LS) screening of metastatic colorectal cancer (mCRC) patients in integrated healthcare delivery organizations. Methods We determined the availability of LS screening criteria and actual LS screening in the medical records among 1,188 patients diagnosed with mCRC between 2004–2009 at seven institutions in the Cancer Research Network (CRN). Results We found infrequent use of LS screening (41/1188). Family history was available for 937 of the 1188 patients (79%). There was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…[15, 16] Moreover, not all individuals who meet high risk criteria undergo evaluation for Lynch syndrome. [1721]…”
Section: Introductionmentioning
confidence: 99%
“…[15, 16] Moreover, not all individuals who meet high risk criteria undergo evaluation for Lynch syndrome. [1721]…”
Section: Introductionmentioning
confidence: 99%
“…Amsterdam criteria and Bethesda guidelines have been developed to identify patients with CRC who should undergo evaluation for Lynch syndrome using criteria mainly based on family cancer history and age at onset . However, these methods are not sensitive enough to detect all patients with Lynch syndrome given that not all meet these criteria, family history is not always reliable or available, and many patients who do meet these criteria remain undiagnosed . In 2005, Hampel et al performed tumor testing on 1066 patients newly diagnosed with CRC and identified 23 patients with Lynch syndrome, 5 of whom (21.7%) did not meet Amsterdam criteria or Bethesda guidelines .…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, Hampel et al performed tumor testing on 1066 patients newly diagnosed with CRC and identified 23 patients with Lynch syndrome, 5 of whom (21.7%) did not meet Amsterdam criteria or Bethesda guidelines . More recently, Cross et al reported that only 11% and 25%, respectively, of patients who met the Bethesda and Amsterdam criteria had undergone evaluation for Lynch syndrome …”
Section: Introductionmentioning
confidence: 99%
“…Management guidelines for these patients are less clear than for those with a germline MMR mutation, and predictive genetic testing for relatives is not available. Several barriers to genetic counseling and testing have been identified in both endometrial and colorectal cancer patients, including insufficient family history collection, lack of referral, insufficient insurance coverage/cost of the appointment, anxiety for the results, lack of interest, patient/family not wanting to know information regarding cancer risks, and lack of understanding regarding benefits of genetic testing and available preventive measures (10, 14, 15). …”
Section: Introductionmentioning
confidence: 99%